Leveraging cultural and relational capabilities for business model innovation: The case of a digital media EMMNE - Malik, Ashish; Sharma, Piyush; Kingshott, Russel; Laker, Benjamin (Elsevier, 2022)
This paper uses an in-depth qualitative case study of a family-owned emerging market multinational enterprise (EMMNE), specializing in digital and electronic media, to explore how EMMNEs can potentially leverage their technological, cultural, and relational capabilities to deliver superior business and relationship quality outcomes for its clients. An in-depth analysis reveals how this EMMNE transformed its business model. Furthermore, building on a firm’s resource-based view (RBV), specifically, dynamic capabilities, this research examines how this EMMNE leveraged its cultural and relational capabilities and created a social and values-based context through HRM practices suited for its contextual conditions. Such a context and organizational capabilities collectively enabled business model innovation to deliver sustained value to its clients domestically and in other emerging markets. We discuss our findings and conclude with implications for theory and practice.